Soluble Tissue Factor Interferes with Angiostatin-mediated Inhibition of Endothelial Cell Proliferation by Lysine-specific Interaction with Plasminogen Kringle Domains - Albrecht, Sybille; Magdolen, Viktor; Herzog, Ute; Miles, Lindsey; Kirschenhofer, Angela; Baretton, Gustavo; Luther, Thomas (Thrombosis and Haemostasis, 2002)
Experimental and clinical data suggest that tissue factor (TF), the major initiator of blood coagulation cascade, as well as proteases and components of the fibrinolytic system are involved in tumor growth at least in some solid tumors via effects on angiogenesis. Whereas the proand anti-angiogenic effects of the plasminogen/plasmin system and plasminogen kringle domains, respectively, are well characterized, the pathways responsible for the pro-angiogenic properties of TF remain poorly understood. To learn more about the biological significance of the recently described binding of plasminogen to the extracellular domain of TF, we examined the effects of soluble TF (sTF) on angiostatin-inhibited proliferation of endothelial cells.In solid phase binding assays, we found that sTF binds specifically to plasminogen, to the plasminogen kringle domains K1-3, K1-5, K4, as well as to mini-plasminogen. Inhibition of binding of plasminogen and its kringle domains to sTF by the lysine analog 6-aminohexanoic acid (AHA) suggests that lysine-binding sites are involved in plasminogen interaction with TF. Moreover, in the presence of sTF, the inhibitory effect of K1-5 on bFGF-mediated HUVEC proliferation was dose-dependently and saturably abolished. This suggests that TF can interfere with the antagonistic effect of K1-5 on endothelial cell proliferation. In contrast, sTF by itself had no effect on the endothelial cell proliferation. Whereas the interference of TF with K1-5-mediated effect was prevented by AHA, this lysine analog did not abolish the proliferation inhibition of K1-5. In conclusion, the binding of sTF to the plasminogen fragment K1-5 seems to antagonize the anti-angiogenic effects of this plasminogen fragment.
Keywords: Tissue factor; plasminogen; angiostatin; HUVEC